(untitled) (MAUSAM, 1965)
The paper presents a study of the limitations imposed by the seismometer and galvanometer constants on the attenuation factor of the circuit, It is seen that the fun range from zero to one of this factor can be used only if (i) Z11 = Z22 and (ii) Rl/Z11 and R2/Z22. are both less than or equal to 1/2, The special case of a seismograph satisfying the Galitzin Conditions has been studied in the light of the above limitations, and a few possible ways of adjusting the various parameters of the seismometer to obtain the optimum magnification considered.